KAJIAN SOSIOLOGI SENI MASJID AL-IRSYAD PARAHYANGAN BANDUNG - Elianna Gerda Pertiwi (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2023)
Bandung Al-Irsyad mosque is a mosque with a unique form of architecture resembles the Ka’bah. Designed by Ridwan Kamil, this building become famous building in the world. A prestigious award as the five major building of the year 2010 by the National Frame building Association, this mosque become one of the Bandung mainstay tourist destination. This research focus is to dismantle the art contruction suport in the journey of Bandung Al-Irsyad mosque into a high art. To understand the social precesses of this mosque, using the approach in his sociology by Zolberg “Construsting a Sociology of the Art” which suggests that the phenomenon of art is influenced by a social process, the artist, and structural support. This research resulted in the conclution that the creation of a great work of art that could not be separated from the contruction of the rule of art. The artist and the community support for the arts is very important in the development of art work. So that is becomes a high art work. Bandung Al-Irsyad mosque designed by a integrated professional artist with his prestigious awards has received makes this mosque into a very high artist value. Simple and futuristic design is a represent of urban culture. Make it more acceptable to the public.